2022
DOI: 10.3389/fped.2022.934944
|View full text |Cite
|
Sign up to set email alerts
|

Improving Post-discharge Practice of Kangaroo Mother Care: Perspectives From Communities in East-Central Uganda

Abstract: IntroductionKangaroo mother care (KMC) is among the most cost-effective and easily accessible solutions for improving the survival and wellbeing of small newborns. In this study, we examined the barriers and facilitators to continuity of KMC at home following hospital discharge in rural Uganda.MethodsWe conducted this study in five districts in east-central Uganda, within six hospitals and at the community level. We used a qualitative approach, with two phases of data collection. Phase 1 comprised in-depth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…An observational study using in-depth interviews, key informant interviews, and group discussions from communities in east-central Uganda was conducted to examine barriers and facilitators to the continuation of KMC at home. This study found that despite the widespread acceptance of KMC by community health workers, mothers practiced KMC for less time at home than in the hospital [ 17 ]. In contrast, in our study, the KMC duration was maintained in HBKMC.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study using in-depth interviews, key informant interviews, and group discussions from communities in east-central Uganda was conducted to examine barriers and facilitators to the continuation of KMC at home. This study found that despite the widespread acceptance of KMC by community health workers, mothers practiced KMC for less time at home than in the hospital [ 17 ]. In contrast, in our study, the KMC duration was maintained in HBKMC.…”
Section: Discussionmentioning
confidence: 99%